The effectiveness of the problem-based learning model using peer assessment in vocational high school - Aulia Anggraini; Sudiyanto Sudiyanto; Cicilia Dyah Sulistyaningrum Indrawati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aimed to determine the effectiveness of the effect between the Problem-Based Learning model using Peer assessment and the Problem-Based Learning model on student competencies. The study used a quantitative experimental approach at SMK Negeri 1 Sragen in class XI AK 4 as a control class and XI AK 5 as an experimental class. The population involved all XI Accounting class students totaling 160 students, while the sample consisted of 64 students divided into the experimental class and the control class. The results showed that the first hypothesis obtained Fcount data>Ftable or 5.214> 2.760 and sig values. 0.026 <0.05, then Ho is rejected, and Ha is accepted. Learning using the Problem-Based Learning model with Peer Assessment has an average value of 83.78, higher than the average value of the Problem-Based Learning model that is equal to 81.53. This study concludes that there are differences in the effect between the control class and the experimental class on student competence. The experimental class using the Problem-Based Learning Model using Peer Assessment is more effective than the control class using the Problem-Based Learning model.